Optimal design of photovoltaic solar systems considering shading effect and hourly radiation using a modified PSO algorithm. (October 2019) - Shams, Mohammad Hossein; Kia, Mohsen; Heidari, Alireza; Zhang, Daming
Regarding the significant potential of solar energy in Iran, implementation of optimally designed photovoltaic (PV) systems can be effective. Hence, this study proposes two objective functions: first, the maximum possible output energy for a given area and, second, the minimum area receiving a given yearly energy from PV fixed collectors in a solar field, both of which are calculated. In addition, the shading and masking effects are considered in the calculations. A modified particle swarm optimization (MPSO) algorithm is used to solve the optimization problem. The case study of this article is a shopping center in Isfahan-Iran (latitude 32.5°N) with the minimum yearly energy demand of 171 MWh and the 5000 m 2 roof area. To evaluate the yearly energy, the calculated hourly radiation approach is applied to the case study. The results show that the maximum possible generated energy is 881 MWh/year for the given area. In addition, to provide the minimum demand, 720 m 2 area of roof is needed. To verify the effectiveness of the proposed MPSO, the results are compared with those of obtained by the relevant commercial software.